Resistencia bacteriana y consumo de antibióticos de reserva del servicio 7b-unidad de cuidados intensivos del hospital nacional edgardo rebagliati martins – essalud durante los años 2007 y 2008, lima – perú - Miranda Gambini, Zugeily del Pilar (2009)
The present study was made in the Edgardo Rebagliati Martins National Hospital during the year of pharmaceutical boarding school. The objective of this study was to determine the bacterial resistance and consumption of reserve antibiotics. This study consisted in the collection of 127 patients antibiograms in the service Care Unit 7B Intensive, that were obtained from the clinical history of patients hospitalized in this service. The annual consumption of reserve antibiotics was determined for two years of study. The results showed that the bronchial secretion was obtained the highest number of isolated bacteria (in 2007 27.54% and 24% in 2008.) followed by venous catheter Central and blood. The most frequent organism isolated in two years was Pseudoma aeruginosa (2007 17.39% and 24.14% in 2008), this bacterial showed to be the most multiresistance. The highest resistance was to Cefepime and the lowest resistance was to Vancomycin (4.16% in 2007 and 0.0% in 2008). Imipenem was the higher antibiotic consumption in both years with 0.544 DDD/100 day in 2007 and 0.550 DDD/100 day in 2008. The lowest antibiotic consumption in 2007 was to Meropenem with 0.0 DDD/100 day and in 2008 was to Aztreonam (0.009 DDD/100 day)